Cytologic, histopathologic, and clinical features of granulomatous colitis in a French Bulldog. (3rd May 2021) - Conrado, Francisco O.; Jones, Emery A.; Graham, Erin A.; Simpson, Kenneth W.; Craft, William F.; Beatty, Sarah S. K.
Abstract: A young French Bulldog was presented with clinical signs of chronic gastrointestinal disease, unresponsive to medical therapies. Parasite screenings and abdominal ultrasound failed to identify the etiology of the clinical signs. Cytologic evaluation of a rectal scraping sample diagnosed presumptive granulomatous colitis (GC) based on the presence of numerous macrophages with characteristic abundant, pink, granular cytoplasm, which showed an intense pink color when stained with periodic acid‐Schiff. Tissue biopsy samples and Escherichia coli fluorescence in situ hybridization analysis confirmed the cytologic diagnosis. The cytologic, histopathologic, and clinical features and staining properties of GC in a French Bulldog are reported. Rectal scraping should be considered a part of the diagnostic evaluation in patients with suspected GC.